Budaya Organisasi Penanganan Pembiayaan Murabahah Bermasalah - Fuadi, Septiyan Hudan (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2024)
This research examines the factors that cause problematic murabahah financing at BMD Syariah Barat Magetan, and discusses the organizational work culture that is effective in finding solutions to resolve them. This research is field research using qualitative methods. The results of the research show that there are 2 factors that cause financing problems, namely internal factors originating from managerial and governance from the institution, and external factors originating from the customer's economic conditions. This research explains that there is an effective organizational work culture model to reduce the number of problematic murabahah financing, namely rescheduling and the most dominant one is billing customers' homes outside of working hours